Analisis Dampak Industri Kuliner Terhadap Pertumbuhan Ekonomi Lokal di Kabupaten Buleleng - Duwika, Kadek; Samudra , Gede Bandem (Cattleya Darmaya Fortuna, 2024)
This article analyzes the economic impact of the culinary industry on local economic growth in Buleleng Regency. The study employs secondary data from the Central Bureau of Statistics (BPS) and field surveys conducted on culinary businesses in the region. The findings indicate that the culinary industry significantly contributes to local income, employment absorption, and tourism attraction enhancement. Specifically, the culinary sector's contribution to the Gross Regional Domestic Product (GRDP) of Buleleng has increased from 8% in 2018 to 10% in 2023. Additionally, the sector provides employment for approximately 15,000 local workers, reducing the unemployment rate and improving local livelihoods. The annual Buleleng Culinary Festival has become a major tourist attraction, drawing around 50,000 visitors and generating an estimated Rp 25 billion in economic activity. This study highlights the crucial role of the culinary industry in driving local economic growth and recommends continuous support from local government to further develop and promote this sector.